الجمعيات الوطنية الليبية ودورها في الاستقلال (Comprehensive Journal of Science, 2025)
This research examines the topic of Libyan national associations and their role in achieving independence, highlighting the emergence of the Libyan national movement during the Italian occupation (1911–1943). It explores the major political and social transformations that led to the rise of organized national action, shifting from armed resistance especially during the era of Omar Al-Mukhtar to structured political and institutional efforts both inside Libya and abroad.The study reviews the conditions preceding the formation of national associations, including the collapse of traditional political structures, economic and social deterioration, and oppressive colonial policies. Within this context, national associations emerged as key instruments for preserving national identity and promoting political awareness through cultural, social, and indirect political activities inside the country.The research also analyzes the role of Libyan associations in exile, particularly in Egypt, where they contributed significantly to internationalizing the Libyan. Through diplomatic efforts such as organizing conferences, submitting memoranda, and engaging with major powers, these associations succeeded in bringing the Libyan issue before the United Nations, which eventually endorsed Libya’s independence.Furthermore, the study highlights the role of these associations in unifying the Libyan national front across the three regions—Cyrenaica, Tripolitania, and Fezzan—overcoming regional divisions and forming a unified national vision. This unity paved the way for independence in 1951. The research also emphasizes the contribution of the National Constituent Assembly in drafting the independence constitution, establishing a constitutional monarchy, and laying the foundations of the modern Libyan state.In its evaluation, the study concludes that national associations were the primary driving force behind Libya’s transition from resistance to statehood, despite facing challenges such as limited resources and internal disagreements. Their influence extended beyond independence, as they actively participated in state-building and political stabilization.The research ultimately concludes that Libyan national associations played a central and decisive role in achieving independence and establishing the modern Libyan state through unifying national efforts, international advocacy, constitutional development, and institutional formation.